Evaluation of Nutritive and Antioxidant Properties of Blanched Leafy Vegetables Consumed in Northern Côte d’Ivoire - Oulai Patricia D.; Zoué Lessoy T.; Niamké Sébastien L. (Polish Journal of Food and Nutrition Sciences)
The aim of this study was to evaluate the effect of steam blanching processing on the nutritive value and the antioxidant properties of five leafy vegetable species (Amaranthus hybridus, Andasonia digitata, Ceiba patendra, Hibiscus sabdariffa and Vigna unguiculata) that are used for sauce preparation in Northern CÔte d'Ivoire. The selected leafy vegetables were subjected to blanching in pressure cooker for 15, 25 and 45 min and the physicochemical properties were determined using AOAC methods. The result of the study revealed that longer time of blanching (higher than 15 min) caused negative impact by reducing nutritive value but positive impact by reducing anti-nutrients and increasing polyphenols. The registered losses (p0.05) at 15 min were as follow: ash (0.08-10.01%), proteins (0.36-12.03%), vitamin C (19.56-68.67%), carotenoids (18.91-55.48%) oxalates (3.58-21.39%) and phytates (10.51-68.02%). The average increase of polyphenols contents at 15 min of blanching was 1.61 to 30.72%. In addition, a slight increase (0.35-4.16%) of fibres content was observed in the studied blanched leafy vegetables. Furthermore, after 15 min of blanching time the residual contents (p0.05) of minerals were: calcium (264.88-844.92 mg/100 g), magnesium (49.45-435.43 mg/100 g), potassium (675-1895.41 mg/100 g), iron (14.54-70.89 mg/100 g) and zinc (9.48-36.46 mg/100 g). All these results suggest that the recommended time of domestic blanching must be less than 15 min for the studied leafy vegetables in order to contribute efficiently to the nutritional requirement and to the food security of Ivorian population